(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Hodgkin lymphoma (HL) is a highly curable malignancy. It is a unique neoplasm, in which the malignant cell is the Reed-Stenberg cell (RSC); it constitutes approximately 40% of all lymphomas that present during childhood. Objective: To obtain local data on the pattern of childhood and adolescent HL in our community at presentation and then compare it with the international figure. Methods: Eighty-five patients with newly diagnosed pediatric HL were admitted to Hiwa Hematology/Oncology Hospital in Sulaimaniya province of Iraqi Kurdistan were included in this study, they were studied prospectively from March 2006 to March 2014. The patients staged by Ann Arbor Staging system and categories into three risk group depending on the Stage and Number of Nodal Sites and the presence of Bulky Disease. Data analyzed using SPSS software; version 13 and P-value obtained by Chi-square test. Results:The median age at diagnosis was about 13.7 years with peak age of incidence was between 15-18 year and with male predominance. Most common site of the primary tumor was cervical lymph nodes; nodular sclerosis was the most common histopathological subtype and the majorities were presented in stage IIA. Conclusion: The stage in this study was age dependent but neither there was relation between the site of the primary tumor and the risk categories nor relation between risk categories and sex. Keywords: Hodgkin lymphoma, stage, sex distribution, risk category Citation: Abdallah BK, Rashid NG, Tawfiq SA. Pediatric Hodgkin lymphoma in Iraq-KRG-Sulaimani. Iraqi JMS. 2019; 17(1): 12-17. doi: 10.22578/IJMS.17.1.3.